60.8k views
0 votes
Solve the the following for t: th k fd fd At fd- Ot-h fdk t fd h

Solve the the following for t: th k fd fd At fd- Ot-h fdk t fd h-example-1
User Prabu
by
5.7k points

1 Answer

3 votes

We are given the following equation


th-k=fd

We are asked to solve this equation for t.

So that means we have to separate the variable t.

Step 1:

Add k to both sides of the equation


\begin{gathered} th-k+k=fd+k \\ th=fd+k \end{gathered}

Step 2:

Divide both sides of the equation by h.


\begin{gathered} (th)/(h)=(fd+k)/(h) \\ t=(fd+k)/(h) \end{gathered}

As you can see, we have solved the equation for t.

Therefore, the correct option is A.

User Gabbie
by
5.3k points